2007
DOI: 10.1016/j.pediatrneurol.2007.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Spinal Cord Infarction in Children Without Vertebral Fracture

Abstract: Spinal cord infarction in children is a rare condition which is becoming more widely recognized. There are few reports in the pediatric literature characterizing etiology, diagnosis, treament and prognosis. The risk factors for pediatric ischemic spinal cord infarction include obstruction of blood flow associated with cardiovascular compromise or malformation, iatrogenic or traumatic vascular inujury, cerebellar herniation, thrombotic or embolic disease, infection, and vasculitis. In many children the cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 93 publications
(155 reference statements)
0
53
1
2
Order By: Relevance
“…1,2 The abruptness of symptom onset in this case suggests a vascular etiology. Ischemic spinal cord infarction can be caused by decreased blood flow due to hypotension, vascular injury, compression, other impairment or thromboembolism to spinal arteries.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…1,2 The abruptness of symptom onset in this case suggests a vascular etiology. Ischemic spinal cord infarction can be caused by decreased blood flow due to hypotension, vascular injury, compression, other impairment or thromboembolism to spinal arteries.…”
Section: Discussionmentioning
confidence: 73%
“…Ischemic spinal cord infarction can be caused by decreased blood flow due to hypotension, vascular injury, compression, other impairment or thromboembolism to spinal arteries. 1 Acute transverse myelitis is unlikely, as the diagnostic criteria were not fulfilled. 3 Occasionally, acute myelopathy may be misdiagnosed as Guillain-Barre syndrome, as acute spinal shock may present with flaccid paraparesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk factors for this condition were outlined after a recent review of 108 case reports; the most common etiologies were found to be bacterial meningitis, fibrocartilaginous embolism, umbilical arterial catheters and minor trauma (3). There are a small number of case reports describing children with SCIWORA following minor trauma; the exact etiology of spinal cord infarction following minor trauma is not well understood (3). A proposed mechanism is that the relatively inelastic spinal cord is strained inside the more flexible spinal column during either hyperflexion or hyperextension resulting in reactive vasospasm or compression of vertebral and/or spinal arteries.…”
Section: Case 2 Diagnosis: Spinal Cord Infarctionmentioning
confidence: 99%